The Opinions of Farmers on the Cultivation of Fresh Green Soybeans of the Company after Harvesting Rice in Huana Village, Phieng District, Xayabouly Province - NORBOUASAMAI, Fongsamouth; PHOUTHAXAY, Phonesavanh; SIHAR, Phonephasred; chasensong, Keesong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Studying the opinions of farmers towards the cultivation of green soybeans of the company with the purpose of study the satisfaction of farmers towards the cultivation of green soybeans and study the problems, obstacles, and solutions. This study was conducted in Huana Village, Phieng District, Xayabouly Province. The results of the study showed that interviews were implemented with a sample of 52 farmers, using evaluation form for general information, satisfaction in each aspect, problems, and obstacles. Through inquiry and evaluation of satisfaction, it has been shown that the benefit side is satisfied with the company's green soybean cultivation with highest of satisfaction with an average value of 4.07, followed by the service aspect with a satisfaction of 3.58 lying in a lot of satisfaction as well. Moreover, both of each aspect was have a higher present of aspect as 71.63-81.40%, this value was indicated that all farmers were aspect to cultivation of green soybeans of the company. The results of the study of problems, obstacles, solutions and suggestions of farmers, there were 52 interviewees who showed the opinion that: the priority problem was garbage waste 71.15%, ordered by using chemicals 59.61% and the last item was the preparation of soil with depth plowing 55.78%. For the requirements of the farmers, they want the company to encourage people to grow and sell soybean to the company. To increase their rental fee for growing soybeans approximately 51.92%, and to propose the company and government section organize training for farmers to understand about the process of growing soybeans and make people aware of it, which is showed 48.08% respectively.